Analisis Kreativitas dan Minat Siswa terhadap Pembelajaran Seni Rupa SD Negeri 2 Purwosari - Avillyana Putri, Risma; Eka Febiyanti, Venita; Wijayanto, Wasis (Universitas Sultan Ageng Tirtayasa, 2025)
This research aims to determine students' creativity and interest in fine arts at SD Negeri 2 Purwosari. Fine art is a branch of art with media that can be captured by the eye and felt by touch. In fine arts there are various kinds of art, one example is painting or it can be called drawing. This type of research is qualitative research using a case study approach. The data sources in the research were homeroom teachers and elementary school students at SD 2 Purwosari Kudus. The results showed significant variations in art interest between low class and high class. Lower class students are more interested in the fine art of painting, this is due to the expressive and imaginative nature of painting activities which is appropriate to their stage of development. On the other hand, high class students tend to prefer the fine art of weaving. This reflects their growing interest towards activities that are more complex and require technical skills, as well as the desire to create objects that can be used or have aesthetic value.